AN ANALYSIS OF THE FEMALE IMAGE AND NARRATIVE IN JIA ZHANGKE'S FILMS FROM THE PERSPECTIVE OF FEMINISM - Meng Ning; Wang Qi; Sanghamitra Dalal; Guan Shuo, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Jia Zhangke's film works present the living conditions of marginalized groups in society with a unique realistic aesthetic, among which female characters are particularly eye-catching. Not only are they on the periphery of the social structure, but they also endure multiple identity dilemmas amid the drastic changes of the modernization process, revealing a neglected yet highly symbolic female experience. This study, based on a feminist theoretical perspective and employing textual analysis, focuses on the following core research questions: How are female characters depicted in Jia Zhangke's films? What complexities do these female roles exhibit at the social, cultural, and psychological levels? How do they seek subjectivity within the macro-narrative of modernization? To answer these questions, this paper selects films such as "Xiao Wu", "Still Life", and "Unknown Pleasures", and conducts an in-depth exploration of the female characters within them. Through the analysis of character construction, narrative strategies, and visual expression, the study reveals how these women seek subjectivity in the interstices of social gender norms and economic changes, while also examining their complexities in terms of spatial mobility, emotional attachment, and individual resistance. The research finds that Jia Zhangke, through his delicate cinematic language and non-traditional female narratives, presents the coexistence of passivity and agency of women in social transformation, reflecting the deep contradictions in gender relations during the process of modernization. This study aims to further deepen the academic discussion on female characters in Jia Zhangke's films and promote multi-dimensional research on the interwoven influences of gender, class, and modernity, providing important insights into the survival status of contemporary Chinese women.